Irrigation by porous capsule I.Construction of capsules and water release - Silva, Dinarte Aéda da; Araújo, José Venilson de; Silva, Aderaldo de Souza; Gheyi, Hans Raj (Pesquisa Agropecuaria Brasileira, 2014)
The present study shows the possible use of "taguá", a clay from Cariri region, CE, Brazil, as basic material for construction of porous capsules used in localized irrigation. The porous capsules made up of different proportions of "taguá" and its ash with calcium carbonate plus shale talc showed water release capacity In the range of 0,10 ± 0,02 to 36,00 ± 2,37 1/day under hydrostatic pressures varying from 0,25 to 1,00 m, Some modifications in the previous shape of porous capsules are recommended which besides facilitating interconnection of capsules permits 50% economy in plastic tubing necessary for installation of the system.